Structural determinants of an internal ribosome entry site that direct translational reading frame selection. Issue 14 (18th July 2014) - Ren, Qian; Au, Hilda H.T.; Wang, Qing S.; Lee, Seonghoon; Jan, Eric
Abstract: The dicistrovirus intergenic internal ribosome entry site (IGR IRES) directly recruits the ribosome and initiates translation using a non-AUG codon. A subset of IGR IRESs initiates translation in either of two overlapping open reading frames (ORFs), resulting in expression of the 0 frame viral structural polyprotein and an overlapping +1 frame ORFx. A U–G base pair adjacent to the anticodon-like pseudoknot of the IRES directs +1 frame translation. Here, we show that the U-G base pair is not absolutely required for +1 frame translation. Extensive mutagenesis demonstrates that 0 and +1 frame translation can be uncoupled. Ribonucleic acid (RNA) structural probing analyses reveal that the mutant IRESs adopt distinct conformations. Toeprinting analysis suggests that the reading frame is selected at a step downstream of ribosome assembly. We propose a model whereby the IRES adopts conformations to occlude the 0 frame aminoacyl-tRNA thereby allowing delivery of the +1 frame aminoacyl-tRNA to the A site to initiate translation of ORFx. This study provides a new paradigm for programmed recoding mechanisms that increase the coding capacity of a viral genome.